2018
DOI: 10.21149/9193
|View full text |Cite
|
Sign up to set email alerts
|

Smoking susceptibility as a predictive measure of cigarette and e-cigarette use among early adolescents

Abstract: Objective: To assess the validity of a standard measure of smoking susceptibility for predicting cigarette and e-cigarette use in a sample of early adolescents in Argentina and Mexico. Methods: A school-based longitudinal survey was conducted in 2014–16 among secondary students. We analyzed students who were never smokers of regular cigarettes or e-cigarettes at baseline and completed both surveys. The main independent variable was smoking susceptibility. Multilevel logistic regression models were used, adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…We included two of the three items in the Pierce’s scale of susceptibility to smoking (copyright: freely available in the public domain), [ 43 ] which has been shown to predict smoking initiation and progression, [ 44 ] and we replaced cigarettes with ECs to assess adolescent susceptibility to EC use. The two items that we used were “Do you think you will use e-cigarettes in the next 12 months” and “Will you use e-cigarettes if one of your good friends offers you one?”, with the same options “definitely not”, “probably not”, “probably yes” and “definitely yes”.…”
Section: Methodsmentioning
confidence: 99%
“…We included two of the three items in the Pierce’s scale of susceptibility to smoking (copyright: freely available in the public domain), [ 43 ] which has been shown to predict smoking initiation and progression, [ 44 ] and we replaced cigarettes with ECs to assess adolescent susceptibility to EC use. The two items that we used were “Do you think you will use e-cigarettes in the next 12 months” and “Will you use e-cigarettes if one of your good friends offers you one?”, with the same options “definitely not”, “probably not”, “probably yes” and “definitely yes”.…”
Section: Methodsmentioning
confidence: 99%
“…Response options for this question included: “Definitely not”, “not likely”, “likely”, and “definitely”. As is commonly done in tobacco research, we dichotomized responses into not susceptible (“definitely not” response) and susceptible (all other responses) (Morello et al, 2018; Pierce et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, future legalization of e-cigarette products may change e-cigarette consumption patterns, including their relationship with smoking cessation. Even if e-cigarettes may help smokers quit smoking, they may also promote the use of nicotine products among Mexican adolescents, among whom those at a relatively low risk appear interested in trying e-cigarettes 36,37 and are likely to progress to conventional smoking after e-cigarette trial, 38 as found in US studies. 39 Thus, policy makers need to carefully consider both the potential benefits and the potential harm of e-cigarette use for public health.…”
Section: Discussionmentioning
confidence: 99%